Blockchain technology enabling the Physical Internet: A synergetic application framework - Meyer, Tobias; Kuhn, Marlene; Hartmann, Evi (Computers & Industrial Engineering, 2019)

Decarbonizing road freight transportation – A bibliometric and network analysis - Meyer, Tobias (Transportation Research Part D-Transport and Environment, 2020)
Road freight transportation literature increasingly concentrates on environmental aspects to reduce logistics contribution to carbon dioxide emissions. Some literature reviews highlight specific mitigation and adaptation strategies, but the overarching research directions to identify emerging areas and general trends of the field have not yet been clustered or synthesized. This paper presents a systematic quantitative review of the road freight transportation decarbonization literature leveraging bibliographic coupling and network analysis techniques. It contributes to the understanding of road freight decarbonization and provides recommendations for further investigations of the field by systematically mapping the literature body. This way, key research clusters are outlined and visualized to understand the underlying knowledge structure. The findings reveal a diverse and fast-growing research field, which in large parts focuses on route optimizations, last-mile solutions, and alternative fuels, while offering future research opportunities that address organizational barriers currently hindering collaboration and technological or operational measures for long- haul transportations.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Bibliographic coupling; Decarbonization; Green logistics; Literature review; Network analysis; Road freight transportation

How Organizations Prepare for the Future: A Comparative Study of Firm Size and Industry - Meyer, Tobias; von der Gracht, Heiko A.; Hartmann, Evi (IEEE Transactions on Engineering Management, 2020)
The question of how companies can best prepare for the future to maintain or improve their existing position in the market place has increased its momentum. This article aims to analyze future preparedness as a joint construct consisting of a company's exploitation and exploration capabilities. In this article, we thereby consider exploitation as a firm's strategy to prepare for the future by focusing on its organizational structure and resources, and exploration as its strategy to engage in corporate foresight to anticipate changes in their environment. Previous scholars centered their research on large companies and single industries. In this article, we close this gap by analyzing future preparedness of large companies as well as of small and medium-sized enterprises from 12 different industries. Data were obtained from a heterogeneous sample of 602 companies of the German economy. For data analysis, the measured variables were classified using principal component analysis and compared by means of variance analysis. Our results indicate that companies rather build on exploitation of internal resources than on exploration of their environment. We further present firm size and industry as predictors for future preparedness strategies and found that the scope of future preparedness augments with firm size.<br
Keywords: (Ambidexterity; comparative study; corporate foresight; factor analysis; future preparedness; managerial survey; small and medium-sized enterprise (SMEs); )

Technology foresight for sustainable road freight transportation: Insights from a global real-time Delphi study - Meyer, Tobias; von der Gracht, Heiko A.; Hartmann, Evi (Futures & Foresight Science, 2022)
Organizations increasingly adopt technologies and logistics measures to improve their social sustainability, reduce transportation-related carbon emissions, or even design their supply chains carbon negative. However, the speed at which this adoption is progressing is not fast enough to address the sustainability challenges of the world today. To gain deeper knowledge about the adoption process of sustainability-related measures in road freight transportation, this paper examines barriers currently hindering a broader market penetration and derives expected timeframes when mass adoption of 14 relevant technologies will occur. Furthermore, the technologies' impacts on the economic, environmental, and social dimensions of sustainability are discussed providing recommendations, on which technologies the respective stakeholders might focus on in the future. Since we want to examines a long-term technology perspective of the next 25 years, we rely on systematic foresight methodology. More specifically, we collect empirical data by use of a real-time Delphi survey, which particularly suits complex and uncertain environments. Our global panel includes 116 experts from 25 different countries. The assessments are grouped into short-term, midterm, midterm to long-term, and long-term developments. The categories shed light on potential drivers and barriers to the implementation of the surveyed technologies. The findings emphasize the need to systematically select suitable measures and promote those that are expected to deliver short-term sustainability improvements to address current deficits in a timely manner. The article further outlines the crucial role of politics in developing necessary regulative frameworks to drive sustainability in road freight transportation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: battery electric trucks; carbon emissions; real-time Delphi survey; road freight transportation; sustainability; technology foresight

The bumpy road to the adoption of the Physical Internet – Overcoming barriers from a stakeholder perspective - Meyer, Tobias; Hartmann, Evi (6th International Physical Internet Conference Proceedings, 2019)
The Physical Internet aims for a paradigm shift by eliminating the unsustainability issues in today’s supply chain processes. The development of the concept in recent years has shown that the PI is still in its conceptualization phase. In order to increase the attention and adoption of the concept both, in literature and practice, empirical knowledge is needed concerning how and why affected stakeholders will adopt the concept. To address this gap, we gathered qualitative data through a single embedded case study approach. In total, we have integrated 14 stakeholders with verifiable expertise in the PI. The sample consists of logistics and transport service providers, shippers and includes companies selling or working on specific PI-products. Furthermore, we gathered empirical data from research institutes with specific knowledge or projects in the PI. This paper provides insights about the adoption of the PI and in particular about stakeholder intentions, organizational and technological readiness as well as barriers and drivers
Keywords: Physical Internet; Case Study; Open networks; Drivers

The research landscape around the physical Internet – A bibliometric analysis - Münch, Christopher; Wehrle, Manuel; Meyer, Tobias; Hartmann, Evi (International Journal of Production Research, 2023)
The concept of the Physical Internet (PI) has been introduced as a vision for globally efficient and sustainable logistics. Examining the activities of the PI since its foundation, enormous efforts can be recognised in the political and business spheres. Furthermore, the topic has received considerable attention from logistics and supply chain management scientists. In this context, a wide variety of dimensions of the PI concept has been investigated. In contrast to some existing qualitative literature reviews, this study focuses on a quantitative review methodology to provide a holistic overview of the PI concept and its underlying dimensions and interrelations. Based on bibliometric performance analysis and science mapping, this research maps and connects the extant PI literature landscape. In doing so, the most important journals, researchers, and institutions in the PI field are identified. Furthermore, eight research topics are grouped thematically, including PI benefits and the challenge of its operationalisation, carriers and shippers in the PI network, PI foundations, smart product-service systems and services, hyperconnected city logistics, information and communication technology requirements, modular PI containers, and organisation and control of PI hubs. Based on the clustering of existing research, the study concludes by providing directions for future researc
Keywords: Physical internet; logistics; supply chain management; bibliometric analysis; bibliometric coupling